Constitution, oxidation and creep of eutectic and eutectoid Mo-Si-Ti alloys. (January 2019) - Schliephake, Daniel; Kauffmann, Alexander; Cong, Xiangna; Gombola, Camelia; Azim, Maria; Gorr, Bronislava; Christ, Hans-Jürgen; Heilmaier, Martin
Abstract: In the present contribution, we describe the successful development of two ternary Mo-Si-Ti alloys with two-phase eutectic and eutectoid microstructure, respectively. In the case of Mo-20.0Si-52.8Ti (at.%), a fully eutectic microstructure consisting of body-centered cubic (bcc) solid solution (Mo, Ti, Si) and hexagonal (Ti, Mo)5 Si3 can be obtained in very good agreement with thermodynamic calculations. A fully eutectoid decomposed microstructure is observed subsequent to heat-treatment at 1300 °C for 200 h in the case of Mo-21Si-34Ti (at.%). For this alloy, bcc (Mo, Ti, Si) and tetragonal (Mo, Ti)5 Si3 appears after decomposition from the A15-type (Mo, Ti)3 Si. Besides that, a small amount of hexagonal (Ti, Mo)5 Si3 forms in the silicide lamellae, too, which is attributed to Ti segregations in the as-cast microstructure. In addition to the focus on microstructure, both oxidation and creep behavior were preliminarily investigated and compared to other state-of-the-art Mo-based alloys. In the case of the eutectic alloy, a promising and unexpected oxidation resistance at 800 °C is observed whereas the eutectoid alloy exhibits catastrophic oxidation; a behavior that is typically observed under these conditions in alloys containing Mo-rich solid solution. The eutectic alloy shows an approximately one order of magnitude higher creep rate within the investigated temperature and stress range as compared to the eutectoid decomposed counterpart. This is attributed to the rather low intrinsic creep resistance of the hexagonal (Ti, Mo)5 Si3 and generally lower melting point of the former alloy, whereas in the latter case, creep seems to be controlled by the deformation of the bcc solid solution (Mo, Ti, Si) and the tetragonal (Mo, Ti)5 Si3 . Graphical abstract: Highlights: Compositions for fully eutectic and eutectoid Mo-Si-Ti alloys were determined. The eutectic alloy consists of (Mo, Si, Ti) and (Ti, Mo)5 Si3 . The eutectic alloy does not exhibit pesting at 800 °C. The eutectoid alloy consists of (Mo, Si, Ti) and mostly (Mo, Ti)5 Si3 . The eutectoid alloy exhibits good creep resistance.